2013
DOI: 10.1007/s12291-013-0365-5
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and Biochemical Parameters in Apparently Healthy Indian Population: Defining Reference Intervals

Abstract: Clinical reference intervals among Indian population are poorly defined. Therefore, there is an urgent need to establish local clinical laboratory reference intervals for healthy Indian population. The present study aimed to identify the 95 % reference interval for hematological and biochemical parameters in apparently healthy Indian population. We undertook a multicentric cross-sectional study conducted at Apollo Hospitals Educational and Research Foundation across India. Of which 10,665 reference individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
3
22
1
Order By: Relevance
“…In another Indian study, the AST reference ranges were reported by Sairam et al for reference population comprising of four Indian cities (Chennai, Hyderabad, New Delhi and Ahmadabad). The RI established in this study for AST was-(12.0-37.0 IU/L for female and 14.0-42.0 IU/L for male) [22]. The RIs of GGT calculated in our study was 7.9-34.6 IU/L for female and 8.6-36.2 IU/L for male.…”
Section: Discussionsupporting
confidence: 49%
“…In another Indian study, the AST reference ranges were reported by Sairam et al for reference population comprising of four Indian cities (Chennai, Hyderabad, New Delhi and Ahmadabad). The RI established in this study for AST was-(12.0-37.0 IU/L for female and 14.0-42.0 IU/L for male) [22]. The RIs of GGT calculated in our study was 7.9-34.6 IU/L for female and 8.6-36.2 IU/L for male.…”
Section: Discussionsupporting
confidence: 49%
“…Compared to other African countries, the total cholesterol reference ranges were similar to one derived from Ivory Coast [ 1 ], Kenya [ 7 ], Tanzania [ 7 ] and Mozambique [ 16 ]. On the other hand, total cholesterol levels in Burkina were higher than those from Benin[ 4 ], Ghana [ 17 ] and Nigeria [ 5 ].Compared to Indian values, total cholesterol values were close to those of Goswami [ 18 ] and Gupta[ 6 ] but lower than those of Madhumita [ 8 ] and Sairam [ 19 ]. Our values were lower than those recorded in France [ 20 ] and in USA [ 7 ].…”
Section: Discussionmentioning
confidence: 67%
“…The levels of serum total protein, globulin, and the A/G ratio were greater than the lower boundary 95% CI for AUC >0.5 and found to be significant. The cutoff values of serum proteins used were the reference intervals for healthy Indian males as reported by Sairam et al [21]. The optimal cut point values for BLL in serum proteins are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%